2020
DOI: 10.1186/s40359-020-00398-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive fatigue in relation to depressive symptoms after treatment for childhood cancer

Abstract: Background: Cognitive fatigue after childhood cancer is frequently overlooked despite guidelines recommending follow-up, and might be mistaken for depression due to overlapping symptoms. Our objectives were: 1) to examine ratings of fatigue in survivors of paediatric brain tumours (BT) and acute lymphoblastic leukaemia (ALL) compared to healthy controls, 2) to examine the relationship between symptoms of depression and cognitive fatigue, and 3) to evaluate parent-child concordance in ratings of cognitive fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 52 publications
10
27
1
Order By: Relevance
“…National tests are mandatory, and there may be different explanations for the higher frequency of missing information among PBTS. Mental fatigue is a common problem for PBTS [ 24 , 25 ], and this may affect their capacity to participate in the national tests, which are time-consuming and may require substantial effort. Another explanation for the missing information could be that PBTS generally have high school absences [ 26 , 27 , 28 ] and, therefore, happened to be absent at the time of the tests.…”
Section: Discussionmentioning
confidence: 99%
“…National tests are mandatory, and there may be different explanations for the higher frequency of missing information among PBTS. Mental fatigue is a common problem for PBTS [ 24 , 25 ], and this may affect their capacity to participate in the national tests, which are time-consuming and may require substantial effort. Another explanation for the missing information could be that PBTS generally have high school absences [ 26 , 27 , 28 ] and, therefore, happened to be absent at the time of the tests.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors rated themselves to have more cognitive fatigue as compared to general fatigue and sleep/rest fatigue (M = 48.43, SD = 26.80). Cognitive fatigue scores were poor when compared to those reported in healthy controls in Swedish (M = 76.04, SD = 14.75) and Dutch (M = 76.46, SD = 14.53) samples (Gordijn, Cremers, Kaspers, & Gemke, 2011;Irestorm et al, 2020). Impairment on the fatigue subscales was defined as a score below the 10 th percentile of healthy children and adolescents.…”
Section: Neurocognitive Variables and Measures Of Fatiguementioning
confidence: 99%
“…Cognitive fatigue in children has been investigated in relation to multiple sclerosis (Goretti et al, 2012), traumatic brain injuries (de Kloet et al, 2015), cancer (Meeske, Katz, Palmer, Burwinkle, & Varni, 2004;Varni, Burwinkle, Katz, Meeske, & Dickinson, 2002), sickle cell disease (Panepinto et al, 2014), and rheumatic diseases (Varni, Burwinkle, & Szer, 2004). Survivors of paediatric brain tumours have been shown to suffer from more cognitive fatigue compared to survivors of leukaemia (Irestorm, Tonning Olsson, Johansson, & Ora, 2020;Meeske et al, 2004;Mulrooney et al, 2008). While most follow-up protocols after cancer treatment do not yet include measurements of fatigue, there is an increased demand for including it in followup protocols for survivors of both paediatric and adult cancer (Berger, Mitchell, Jacobsen, & Pirl, 2015;Irestorm et al, 2020;Limond et al, 2020;Tomlinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data reported in the meta-analysis by Swartzman et al 6 , cancer survivors seem to have 1.66 times the odds of post-traumatic stress disorder (PTSD) compared with controls who did not have cancer, but it would seem that the prevalence of adjustment disorder among cancer survivors exceeds that of PTSD, with a prevalence equal to 12.4%. 7 Other studies have found an increase in cognitive fatigue and depressive symptoms in childhood cancer survivors 8 and a considerable percentage is affected by suicide ideation decades after having survived cancer. 9 Comparatively, few descriptions exist of positive psychosocial factors after cancer, even though it has been shown that more than 80% of survivors of childhood cancer report at least one positive consequence of this experience.…”
Section: Introductionmentioning
confidence: 99%